Castles and colonists an archaeology of Elizabethan Ireland - Klingelhöfer, Eric C. (Manchester Spenser., 2010)
Based on decades of research, this volume details how archaeology had revealed the traces of a short-lived, but significant culture which has been, until now, eclipsed ideological conflict between Tudor queens, Hapsburg hegemony and native Irish traditions.